2019
DOI: 10.1177/0959651819875914
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of a hydraulic motor drive with variable inertia flywheel

Abstract: A flywheel is presented in this article, which can adaptively generate variable inertia in response to the application requirements in a hydraulic drive. The said flywheel consists of four sliders in the guide track of a host flywheel frame which change its position as the rotational speed of the flywheel varies. The varying distance between the slider and the center of rotation leads to a variable inertial mass. This passive inertial mass has a potential to reduce the speed fluctuations of the drive. A compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Kondoh et al [14] proposed a new type of flywheel energy storage system in which the moment of inertia is controlled actively for charging and discharging without a power electronic interface while the rotational speed is held almost constant. Concerning a hydraulic drive, a comparative study has been conducted on the effects of the variable inertia flywheel on the hydraulic motor speed fluctuations compared with those of the fixed inertia flywheel in the literature [15]. The results showed that the variable inertia generated by the variable inertia flywheel can better reduce the hydraulic motor speed fluctuations in response to the changes in the excitation inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Kondoh et al [14] proposed a new type of flywheel energy storage system in which the moment of inertia is controlled actively for charging and discharging without a power electronic interface while the rotational speed is held almost constant. Concerning a hydraulic drive, a comparative study has been conducted on the effects of the variable inertia flywheel on the hydraulic motor speed fluctuations compared with those of the fixed inertia flywheel in the literature [15]. The results showed that the variable inertia generated by the variable inertia flywheel can better reduce the hydraulic motor speed fluctuations in response to the changes in the excitation inputs.…”
Section: Introductionmentioning
confidence: 99%